Evolutionary history of the endangered Sanje mangabey (Cercocebus sanjei) in the Udzungwa Mountains, Tanzania: inferences from phylogeography and historical niche modelling - Christina Lynette Paddock; Maria Joana Ferreira da Silva; Gráinne Michelle McCabe; David Fernández; William Scott McGraw; Michael William Bruford (Primates, 2026)
Understanding whether a species’ distribution results from recent and/or anthropogenic events or ancient vicariant factors is critical for conservation planning. The Endangered Sanje mangabey ( Cercocebus sanjei ), endemic to Tanzania’s Udzungwa Mountains, is currently divided into two populations located approximately 100 km apart. These represent distinct evolutionary lineages that diverged around 0.77 million years ago (MYA). We aimed to investigate i) the phylogeographic history and recent changes in size and range of the two Sanje mangabey populations, and ii) whether lack of suitable habitat between populations and consequent difficulty to disperse may have influenced the 0.77 MYA divergence time. We used 64 mitochondrial control region sequences obtained from non-invasive DNA. The probability of suitable habitat across Tanzania and the Udzungwa Mountains was modelled at three time points: Mid-Holocene (6,000 YA), Last Glacial Maximum (22,000 YA), and the Last Interglacial period (120,000–140,000 YA). We found six haplotypes, clustered into two haplogroups. Significant differentiation was estimated between populations, which show no evidence for recent range expansion or contraction. The ecological niche modelling revealed fluctuating extents of suitable habitat across southern Tanzania. Large genetic differentiation between populations may have been influenced by a general trend in aridification in East Africa across the last 40,000 years, resulting in a shift of montane forests to gradually higher elevations. Intermediate populations may have become extinct as suitable habitat retracted, leaving relict populations with relatively stable demographic histories ancestral to the present-day populations. This study supports their preliminary designation as separate evolutionary significant units, a conclusion with conservation management implications.